Pendekatan Follow The Money Sebagai Instrumen Pembuktian Dalam Perkara Korupsi Dan Pencucian Uang - Nurrurachman, Kevin; Syadid Jiddan Alharun; Agrez Aprianti; Riqa Kurnia Sabilla; Kiki Amaliah (CV. ITTC INDONESIA, 2025)
This scientific work juridically analyzes the position and role of the Follow the Money (FTM) methodology as a vital instrument in proving cases of Corruption (Tipikor) subsequently linked to Money Laundering Crimes (TPPU). FTM is understood as an investigative paradigm that traces the movement of assets derived from crime, which is key to separating the predicate crime (corruption) from the subsequent offense (money laundering). The central issue investigated is how the normative provisions in Law Number 8 of 2010 concerning TPPU provide the legal basis for FTM, particularly through the mechanism of reverse burden of proof and asset forfeiture. Using a normative legal research method, this study highlights implementation barriers of FTM, such as the complexity of penetrating bank secrecy and the need for data synchronization among law enforcement agencies. The findings indicate that FTM is a legal necessity, but its effectiveness highly depends on strengthening the synergy between the Prosecutor's Office, Police, and PPATK, and the progressive application of law to achieve maximum state loss recovery.